Sumbangan Pemikiran Hak Asasi Manusia Terhadap Pembaharuan Kitab Undang-Undang Hukum Acara Pidana (KUHAP) - Ari Wibowo (Unisia, 2014)
The idea of renewal of the Criminal Procedure Code can not be separated from the conceptualcontribution of Human Rights (HAM). This contribution has been explicitly included in thepreamble of the draft of Criminal Procedure Code. Although the current Criminal ProcedureCode already provides protection to the rights of the suspect or the accused, but theimplementation is still not optimal. Therefore, in the draft of Criminal Procedure Code there isa new institution called the Judicial Commissioner (Rechter-Commissaris) to replace thefunction of Pretrial institutions. The Judicial Commissioner has far wider powers of Pretrialinstitution, so that the protection of the rights of suspects or defendants in any stage of thejudicial process will be more secure fulfillment. The development of human rights concept alsocontributed to the idea to regulate the rights of victims in the renewal of the Criminal ProcedureCode. Protection of the rights of victims in the current Criminal Procedure Code is limited tothe rights to the incorporation of lawsuits for damages to the criminal case. Because it has notadequately regulated in the current Criminal Procedure Code, the draft of Criminal ProcedureCode regulates the rights of victims, both associated with involvement in all stages of judicialproceedings and the right to sue for damages.